Multimodal Model Performance on Low-Resource Diagram Understanding in HumanEval-V - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 13 peer-reviewed papers addressing the following research question: How do multimodal models compare in performance on HumanEval-V tasks when evaluated for low-resource diagram understanding with limited training data. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 3.7/10. This report is a machine-generated literature synthesis and d
Machine-generated literature synthesis.